Barriers and facilitators of public transport use among people with disabilities: a scoping review - Mwaka, C. R.; Best, K. L.; Cunningham, C.; Gagnon, M.; Routhier, F. (Frontiers in Rehabilitation Sciences, 2024)
Barriers to public transport use may be experienced differently by people with various types of disabilities (e.g., physical, intellectual, cognitive, sensory). Thus, it is important to identify the variable needs within each element of the travel chain. For example, the unavailability or low volume of auditory announcements in a stop or station or on the public transport vehicle may be a barrier to people with visual disability who rely on hearing the information. Consequently, this could provoke negative emotions and unpleasant experiences, which may not be the case for people with physical disabilities. The primary objective was to describe the barriers and facilitators to using public transport experienced by people with disabilities (PWD). The secondary aim was to explore experiences in terms of self-efficacy and satisfaction, when using public transport among people with disabilities. A scoping review was conducted. The search was performed in MEDLINE, TRANSPORT DATABASE, PsycINFO, EMBASE, and WEB OF SCIENCE from 1995 to 2023. Of 6,820 citations identified, 34 articles were included in the review for extraction. The main physical and social barriers included lack of ramp, long walking distance, long waiting time, unavailability of information at bus stop or station, and drivers' negative attitudes towards PWD. Personal factors that prevented the use of public transport included lack of confidence, and decreased satisfaction with public transport use. Strategies such as providing ramps on public transport vehicles, availability of kneeling buses and courtesy of bus drivers, and travel training were considered as enablers to the use of public transport that can lead the improved self-efficacy and satisfaction. In conclusion, this review identified the physical and social barriers and facilitators in travel chain, and highlighted issues related to lack of confidence or self-efficacy and decreased satisfaction when PWD and older adults are using public transport. Identifying and understanding the barriers and facilitators to the use of public transport by PWD is a milestone that may help policy makers and transport operators around the world to develop and implement interventions enabling access, use and inclusion of this mode of transport, as the experiences of PWD when using this mode of transport have an impact on their well-being.